Combined Mining Technologies for Coal Deposits (Review) - A. Yu. Ermakov (Горные науки и технологии, 2019)
The paper discusses the main disadvantages of strip and underground mining methods and possibilities of eliminating the disadvantages through introducing a combined technology of coal deposit mining. Combined coal mining technology is the method comprising elements of several geotechnologies, for example, underground and strip mining, as well as, possibly, underwater mining, borehole and other techniques of deposit mining. The combined coal mining technology provides for unified layout for opening, development, production and processing of reserves for the whole LoM on the basis of general technological solutions made in advance. Such complex solutions for opening and development of deposit reserves within the opencast and underground mining contour allows minimizing the volume of openings and reducing the time for commissioning, investment costs, as well as decreasing the costs for aerage, drainage, rock mass hauling and land reclamation. Substantiation of deposit opening options should comprehensively take into account technical, organizational, and economic factors [34–37]. Analysis of the options as exemplified by the Makar’evskoe coal deposit development in Kuzbass allows to conclude that the combined method is promising and promotes increasing optimal volumes of coal production, while reducing the deposit development time by about 15 %, and increase the net present value compared to underground and opencast mining options more than 5 times.